급성 폐혈전색전증 전국 실태 조사 보고 - 대한결핵 및 호흡기학회 급성 폐혈전색전증 전국 실태 조사 소위원회; Scientific Committee for National Survey of Acute Pulmonary Thromboembolism, Korean Academy of Tuberculosis and Respiratory Diseases (Tuberculosis and respiratory diseases, 2003)
Background : According to the study in ICOPER (International Cooperative Pulmonary Embolism Registry), the overall mortality rate of acute pulmonary thromboembolism (APTE) at 3 months is 17.4%. According to the study for current status of APTE in Japan, the hospital mortality rate is 14%. Although the incidence and mortality rate of APTE has been increasing, patient characteristics, management strategies, and outcome of APTE in the Korean population have not yet been assessed in large series. We therefore performed the national survey for the current status of APTE in the Korean population. Methods : 808 registry patients with APTE were analyzed with respect to clinical characteristics, risk factors, diagnostic procedures, treatment, and clinical outcome. Results : Main risk factors were immobilization, recent major surgery, and cancer. Common symptoms were dyspnea and chest pain. Common signs were tachypnea and tachycardia. The majority of registry patients underwent lung perfusion scanning. Spiral CT was used in 309 patients(42.9%), and angiography in 48 patients(7.9%). Heparin was the most widely used treatment. On multivariate logistic regression analysis, onset in hospital (odds ratio 1.88, p=0.0385), lung cancer (odds ratio 9.20, p=0.0050), tachypnea (odds ratio 3.50, p=0.0001), shock (odds ratio 6.74, p=0.0001), and cyanosis (odds ratio 3.45, p=0.0153) were identified as significant prognostic factors. The overall mortality rate was 16.9% and mortality associated with APTE was 9.0%. Conclusions : The present registry demonstrated the clinical characteristics, diagnostic strategies, management and outcome of patient with APTE in Korea. The mortality rate was 9.0%, and the predictors of mortality were onset in hospital, lung cancer, tachypnea, shock, and cyanosis. These results may be important for risk stratification as well as for the identification of potential candidates for more aggressive treatment. 연구배경 : ICOPER 보고에 의하면 급성 폐혈전색전증 발생 3개월내 사망률이 17.4%이며, 일본 조사에서는 사망률이 14%라고 보고하였다. 그러나 국내에서는 급성 폐혈전색전증의 전국 규모의 대단위 연구가 없어서, 그 현황에 대해 보고된 바 없었다. 따라서 본 학회에서는 급성 폐혈전색전증에 대한 전국 실태조사를 시행하였다. 방법 : 1998년 1월 1일부터 2000년 12월 31일까지 전국수련병원급 이상 종합병원에서 급성 폐혈전색전증으로 진단받은 환자를 대상으로 역학적 특성, 임상양상, 진단법, 위험인자, 치료, 임상경과 등을 조사하였다. 결과 : 환자들의 평균연령은 $58.3({±}16.3)$세 였고, 남자가 40.3%였다. 발생 위험인자로는 장기간의 부동상태, 수술, 악성종양이 각각 22.9, 19.2, 15.8% 였다. 가장 흔한 증상으로는 호흡곤란과 흉통이었다. 진단을 위한 검사방법으로는 폐관류 스캔을 시행한 경우가 가장 많았다. 흉부 방사선 검사상 정상 소견을 보인 경우가 53.5%로 가장 많았고, 이상 소견으로는 흉막 삼출액이 가장 흔하였다. 치료방법으로는 86.8%에서 헤파린 항 응고법을 시행하였고 혈전 용해요법은 시행한 경우는 12.3%였다. 사망을 예측할 수 있는 인자로는 병원내에서 이환된 경우, 폐암, 빈호흡, 쇼크, 청색증의 5가지로 분석되었고, 사망 위험도는 각각 1.88, 9.20, 3.50, 6.74, 3.45배 였다. 전체 사망률은 16.9%였고 그 중에서 급성 폐혈전색전증과 연관된 사망률은 9.0%였다. 결론 : 본 조사는 급성 폐혈전색전증에 대한 최초의 전국규모의 실태조사로서, 이 결과가 향후 국내 급성폐혈전색전증의 연구와 치료에 기여할 수 있을 것으로 사료된다.